Thermal Behavior and Spectroscopic Study of Neutral and Cationic Mononuclear Cyclopalladated Compounds - Ananias, Sandra R. [UNESP]; Mauro, Antonio Eduardo [UNESP] (FapUNIFESP (SciELO), 2003)
The reactions of the precursor [Pd(N,C-dmba)(MeCN)2](NO 3) (1) (dmba = N,N-dimethylbenzylamine), with the proligands 3,5-dimethylpyrazole (Hdmpz), 2-quinolinethiol (qnSH) and 1,1′- bis(diphenylphosphine)ferrocene (dppf) afforded the compounds [Pd(N,C-dmba)(Hdmpz)(ONO2)]0.5CH2Cl2 (2), [Pd(N,C-dmba)(qnSH)(ONO2)] 0.5CH2Cl2 (3) and [Pd(N,C-dmba)(dppf)](NO3) (4), respectively. The mononuclear species 2,3 and 4 were characterized by elemental analysis, infrared spectroscopy, NMR and thermogravimetric analysis. The IR spectra show bands which are consistent with terminal monodentate nitrate group for 2-3 and ionic nitrate for 4. The 1H and 13C NMR data confirm that coordination of the organic ligands has occurred and the 31P{1H} NMR data for 4 clearly evidences the occurrence in solution of three cyclopalladated species with the dppf acting as a bridging ligand in two cases and as a chelate in one. The thermal behavior of compounds 1-4 suggests that complex 2 is the most stable. The X-ray diffractometry results show the formation of PdO from 1 and 2, Pd2OSO4 from 3, and of a mixture of PdO and Fe 2(PO4)3 from 4, as final decomposition products.
Keywords: Cyclopalladated species; IR and NMR spectroscopy; Thermogravimetric analysis; 1,1' bis(diphenylphosphine)ferrocene; 3,5 dimethylpyrazole; cation; ferrocene derivative; ligand; nitric acid derivative; palladium complex; pyrazole derivative; quinolinethiol; thiol derivative; unclassified drug; carbon nuclear magnetic resonance; chemical analysis; chemical structure; infrared spectroscopy; nuclear magnetic resonance; precursor; proton nuclear magnetic resonance; reaction analysis; spectroscopy; structure analysis; thermal analysis; thermogravimetry; X ray diffraction